Developing a Vaccine - Ibrahim Mohamed Saeed Shnawa (Vaccines and Vaccine Interference, 2023)
The approach of how newly invented vaccines are developed, evaluated and commercialized are being presented. The developing process implied preclinical and clinicl phases of development. It is described as a strigent settings performed in a sequential manner.